Effects of lasalocid on growth, nutrient digestibility and rumen characteristics in chios lambs and Damascus kids - Hadjipanayiotou, Miltiades; Economides, S.; Papachristoforou, Christakis (My University, 1988)
Two feeding trials and one digestibility trial with early weaned Damascus kids (50 days of age) and one feeding trial with early weanes Chios female lambs (42 days of age) were carried out to investigate the effects of lasalocid sodium (37.5 mg kg−1 feed as fed basis) on growth and incidence of coccidiosis. In the first feeding trial with kids, the effect of protecting the feeding troughs from being contaminated with faeces was also examined. Both the protection of troughs and the addition of lasalocid sodium significantly improved growth of kids in the first trial. Feed utilization was also improved (11%) when a lasalocid containing diet was fed. Addition of lasalocid increased propionate and decreased butyrate relative molar proportions in the rumen. Differences in acetate molar proportion, ruminal pH, NH3-N concentration or total VFA between the diets were not significant. In the second trial, kids fed the lasalocid diet tended to grow faster. Feed efficiency was also improved (7.6%). In the third trial, lambs on the lasalocid containing diet grew faster, but there was no improvement in conversion efficiency. Digestion coefficients (determined with kids) of dry matter, organic matter and crude protein were 0.76, 0.77, 0.69 and 0.78, 0.79, 0.74 for the control and the diet containing lasalocid, respectively. Four clinical cases of coccidiosis were reported in kids fed the control diet (unprotected troughs, no lasalocid) in the first trial and three cases in the no lasalocid diet in the second trial. In the trial with lambs, no clinical case of coccidiosis was recorded.